Inhibition of DNA Repair Enzymes as a Valuable Pharmaceutical Approach - Volcho, Konstantin; Lavrik, Olga (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Although DNA repair enzymes play a crucial role in maintaining the integrity of the genome, the hyperactivity of certain enzymes of the DNA repair system can lead to the resistance of tumors to chemo- and radiotherapy, aimed at damaging the DNA of cancer cells. Therefore, the inhibition of DNA repair enzymes could help to overcome this resistance. The reviews and research articles included in this collection describe the molecular mechanisms of action of some important enzymes of the DNA repair system, as well as some new inhibitors of such enzymes and the pharmacological properties of these inhibitors. This reprint clearly demonstrates the importance of the inhibition of DNA repair enzymes to fight various diseases, especially cancer.